Kidney function is associated to Alzheimer's related blood biomarkers (NfL, P‐tau181, and GFAP) but not dementia risk in a community‐based cohort followed over 17 years. (20th December 2022) - Stocker, Hannah; Beyer, Léon; Trares, Kira; Perna, Laura; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Schöttker, Ben; Gerwert, Klaus Bernhard; Brenner, Hermann
Abstract: Background: In order to determine the future of Alzheimer's disease (AD) related blood biomarkers in the clinical setting, it is crucial to identify factors that could affect the interpretation of biomarker levels. Kidney function has been shown to influence biomarker levels, but has also exhibited associations to dementia risk and it is unclear whether kidney function plays a role in AD pathology or is merely a factor influencing blood biomarker levels. Therefore, the aim of this study was to explore the association of kidney function with risk of incident AD/dementia diagnosis within 17 years and with the blood biomarkers, neurofilament light (NfL), phosphorylated tau (p‐tau181), and glial fibrillary acidic protein (GFAP), in a community‐based cohort study. Methods: Kidney function was assessed through the estimated glomerular filtration rate test (2021‐CKD‐EPI creatinine‐cystatin C equation (eGFRcr‐cys)) at baseline in 6, 256 participants aged 50‐75 years, of whom 510 received a dementia diagnosis throughout 17 years of follow‐up in a community‐based prospective cohort study in Germany (Figure 1 ). In a subset of participants (n=766, n=261 dementia cases), NfL, p‐tau181, and GFAP blood concentrations were measured at baseline using Simoa technology. Cox regression and linear regression models adjusted for age and sex were used to assess the association of kidney function with incident dementia risk and the log‐transformed blood biomarker concentrations. Results: Impaired kidney function (eGFRcr< 60 mL/min/1.73m 2 ) at baseline was not associated to incident dementia (p=.73) or AD diagnosis (p=.94) within 17 years (Figure 2 ). However, the blood biomarkers, NfL and P‐tau181, did exhibit significant associations to impaired kidney function (β, p‐value: NfL, 0.47, <.0001; P‐tau181, 0.21, <.01) and gender‐specific associations were evident in the association to GFAP (β, p‐value: Males, 0.31, <.01; Females, ‐.12, .11) (Table 1 ). Conclusions: Reduced kidney function may result in increased concentrations of AD related blood biomarkers but not necessarily increased AD risk. Kidney function might influence the accuracy of AD blood biomarkers and should be considered in clinical translation. Additionally, the interaction between kidney function and sex in the association to GFAP including possible explanatory biological mechanisms should be further explored.